2014
DOI: 10.1371/journal.pone.0105558
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status in Preeclampsia: Seasonal Changes Are Not Influenced by Placental Gene Expression of Vitamin D Metabolizing Enzymes

Abstract: Preeclampsia, a hypertensive disorder in pregnancy develops in 2–8% of pregnancies worldwide. Winter season and vitamin D deficiency have been associated with its onset.ObjectiveTo investigate the influence of season on maternal vitamin D status and placental vitamin D metabolism.Methods25-OH vitamin D and 1,25-(OH)2 vitamin D were measured in maternal serum obtained during the winter or summer months from 63 pregnant women at delivery (43 healthy, 20 preeclampsia). In a subgroup, mRNA expression of CYP24A1 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
15
1
3
Order By: Relevance
“…In contrast to previous reports describing decreased serum 25(OH)D3 in PET [13,14,31], vitamin D-deficiency was observed for most of the women in the current study, despite this being a predominantly white Caucasian cohort. This may be due to the smaller size and non-matched cohort used [14], or the fact that some studies quantified serum 25(OH)D3 using ELISA technology which cannot distinguish between 25(OH)D3 and 3- epi -25(OH)D3 and may therefore over-estimate serum vitamin D ‘status’ [13,31]. Nevertheless, the over-arching conclusion from data presented here is that simple measurement of serum 25(OH) D3 provides a very limited perspective of vitamin D in pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous reports describing decreased serum 25(OH)D3 in PET [13,14,31], vitamin D-deficiency was observed for most of the women in the current study, despite this being a predominantly white Caucasian cohort. This may be due to the smaller size and non-matched cohort used [14], or the fact that some studies quantified serum 25(OH)D3 using ELISA technology which cannot distinguish between 25(OH)D3 and 3- epi -25(OH)D3 and may therefore over-estimate serum vitamin D ‘status’ [13,31]. Nevertheless, the over-arching conclusion from data presented here is that simple measurement of serum 25(OH) D3 provides a very limited perspective of vitamin D in pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported PET-associated declines in serum 1,25(OH) 2 D3 [31,32], similar to those reported in the current study. This may be due to decreased serum levels of insulin-like growth factor 1 [32], a stimulator of renal 1α-hydroxylase, or lower expression of 1α-hydroxylase in the placenta [33], but other PET studies have reported increased whole human placental tissue 1α-hydroxylase expression [34].…”
Section: Discussionsupporting
confidence: 90%
“…The levels of 1,25-(OH)2D3 in the maternal and umbilical cord are lower in PE than Norm-Preg [57]. PE is more common in winter possibly due to low serum 25(OH)D3 and placental 1,25(OH) 2 D3 levels leading to impaired placentation [58] and up-regulation of TNF-α, IL-6 and IL-1β [59]. Vitamin D receptor null mice show increased plasma renin, plasma ngII, and HTN.…”
Section: Introductionmentioning
confidence: 99%
“…Большое количество генов регулируется с помощью кальцитриола [11,15]. VDR отвечают на воздействие кальцитриола увеличением генной экспрессии 25(OH)D -24-гидроксилазы (CYP24А1), чтобы метаболизировать 25(OH)D и 1,25(OH)2D в биологически инертные водорастворимые неактивные формы (в том числе кальцитроевую кислоту, она растворяется в воде и выводится из организма в составе желчи и мочи) [16][17][18]. Кальцитриол по механизму отрицательной обратной связи подавляет свой собственный синтез и стимулирует собственное разрушение за счет индукции почечного фермента 25-гидроксивитамин D-24-гидроксилазы (CYP24A1).…”
Section: таблицаunclassified